Challenges and countermeasures of China’s research on “sports promoting adolescent socialization”–data mining based on Weibo and CNKI - Jiang, Yueyan; Tao, Baole; Lu, Tianci; Yan, Jun (Frontiers in Psychology, 2023)
This paper improves our understanding of the public demand for adolescent socialization and compares the popular topics in research on sports promoting adolescent socialization to clarify the high-quality development of these activities. Data were collected from Weibo posts about “adolescent socialization” from April 13, 2017, to June 1, 2022, using Python and the Latent Dirichlet Allocation. We used CiteSpace to collect studies in China National Knowledge Infrastructure，which related to the research topic, and created a keyword co-occurrence network to identify key areas of work. A total of 77,900 original Weibo posts were captured. The theme model identified five potential themes: school and family education, social participation, community education, ideological and political education, and media. The semantic network showed that the public concerns of each theme include: adolescent socialization education content, relevant policies and regulations, adolescent socialization environment, traditional culture, and publicity methods and examples. Ultimately, 52 studies were finally retrieved. The keyword co-occurrence network showed that keywords such as adolescent, socialization, sports games, school sports, and family sports appeared most frequently and had the highest intermediary centrality. Research focused on socialization, Internet addiction, coupling, school sports, sports socialization, and media. The public’s attention to adolescent socialization has three characteristics: subject linkage, object susceptibility, and media diversity. The research on sports promoting the socialization of adolescents has some problems, such as the lack of research on the linkage of educational subjects, the relatively backward of educational methods , and the inadequate media publicity. This is because there is an information gap between scholars and the public. Existing research results cannot meet the demands of the public.